Determinants and Income Effects of Small Farmers Selling to Supermarkets versus Traditional Market Channels in Four Regions of India - Nuthalapati, Chandra S; Mishra, Ashok K; Pingali, Prabhu; Reardon, Thomas (Economic and Political Weekly, 2024)
Using endogenous switching regressions to calculate transitional heterogeneity, we built counterfactual scenarios to identify the treatment effects for sellers to supermarkets and sellers to traditional markets. The results support neither a story of stro
Keywords: Market Channels; Supermarkets; Traditional Market; Small Farmers